Evaluating AI Ambient Voice Technology as a Documentation Assistant in Psychiatry – a Proof of Concept Study - Noah Stanton; Aadam Aziz; Solomon Wong; Salim Jakhra; Sirous Golchinheydari (BJPsych Open)
Aims: Artificial Intelligence Ambient Voice Technology (AI AVT) which uses a large language model to summarise clinical dialogue into electronic notes and GP letters has emerged. Although effective in general practice and medical settings, its potential in psychiatry is unknown. In this proof of concept study, we sought to apply AI AVT into clinical practice for a limited duration.